1988
DOI: 10.1109/irps.1988.362205
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Package Cracking During Reflow Soldering Process

Abstract: Surface munt packages are heated up above solder melt ing temperature during reflow soldering process. If t h e p l a s t i c e n c a p s u l a n t h a s absorbed m o i s t u r e , package cracking may occur. In t h i s study, an evaluat i o n method of Lhe package cracking is developed by means of moisture diffusion analysis of p l a s t i c and deformation and s t r e s s analysis of packages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(47 citation statements)
references
References 4 publications
1
46
0
Order By: Relevance
“…Therefore, it is critical to evaluate the strength of internal vapor pressure generated in the package during reflow. The popcorn failure was first postulated by Fukuzawa et al [3] in 1985, and later supported by many publications [4][5][6].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, it is critical to evaluate the strength of internal vapor pressure generated in the package during reflow. The popcorn failure was first postulated by Fukuzawa et al [3] in 1985, and later supported by many publications [4][5][6].…”
Section: Introductionmentioning
confidence: 89%
“…Kitano et al [5] showed that the package cracking is not controlled by the absolute moisture weight gain, rather it is due to the local moisture concentration at the critical interface. Therefore, moisture diffusion modeling is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fick's second law can be applied to describe the moisture diffusion process in polymer materials [1][2][3][4][5][6][7][8][9][10][11][12][13]. According to Fick's second law, moisture diffusion in a material is defined by Fickian diffusion law in three dimensions as follows [23]:…”
Section: Characterization Of Moisture Diffusion and Hygroscopic Swellmentioning
confidence: 99%
“…Many investigations have shown the delamination phenomenon to be closely linked to the processes of heat transfer, moisture diffusion and vapor pressure build-up [1][2][3][4][5][6] during solder reflow. Manufacture induced small voids or defects in interfaces of plastic IC packages due to the thermal expansion mismatch of the packages generally become potential sites for delamination failure and may grow owing to hygrothermal stress concentration and water vapor pressure in the delamination.…”
Section: Introductionmentioning
confidence: 99%